Advanced PowerPoint 2007 - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course builds on the knowledge gained in the introductory and intermediate courses. Here you will learn to create and format tables and charts in a presentation. You will also apply and customize design themes and templates and create and format SmartArt graphics. You will learn how to add multimedia content, add special effects and interactive elements to slides. Finally, you will learn how to finalize your presentation, broadcast it on the web, create handouts and package for a CD or flash drive."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 9, 2013).
Presenter, Pamela Conway.
Keywords: Presentation graphics software; Microsoft PowerPoint (Computer file); Electronic books